2003
DOI: 10.1016/s0194-5998(03)00629-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3-dimensional computed tomography scan to evaluate upper airway patency for patients undergoing sleep-disordered breathing surgery

Abstract: Modification of palatal surgery to increase the lateral dimension of the RP may be a breakthrough in increasing its success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 11 publications
3
47
0
9
Order By: Relevance
“…Schwab 34 proposed that the retropalatal region in patients with OSA was narrowed in the lateral aspect and the contrary, the retropalatal region in nonapneic people was narrowed in the AP dimension 34 . Li et al 20 reported that lateral narrowing of retropalatal region was closely associated with the degree of sleep apnea in their study 20 . In our study, average rate of lateral pharyngeal narrowing was 12% and 7% at the level of SP-PPW and BoT-PPW, respectively in mandibular setback surgery group while it was 5% and 2% at the level of SP-PPW and BoT-PPW, respectively, in bimaxillary surgery group.…”
Section: Reported That 3dmentioning
confidence: 85%
See 4 more Smart Citations
“…Schwab 34 proposed that the retropalatal region in patients with OSA was narrowed in the lateral aspect and the contrary, the retropalatal region in nonapneic people was narrowed in the AP dimension 34 . Li et al 20 reported that lateral narrowing of retropalatal region was closely associated with the degree of sleep apnea in their study 20 . In our study, average rate of lateral pharyngeal narrowing was 12% and 7% at the level of SP-PPW and BoT-PPW, respectively in mandibular setback surgery group while it was 5% and 2% at the level of SP-PPW and BoT-PPW, respectively, in bimaxillary surgery group.…”
Section: Reported That 3dmentioning
confidence: 85%
“…Skeletal maxillary and mandibular changes may be described by the change in the sagittal dimension only, whereas the soft tissue pharyngeal changes must be considered in a 3D way 7 . CT scan is a noninvasive technique that permits a detailed 3D assessment of the entire upper airway and has been validated for quantitative measurements of the pharyngeal CSA 20 . Kawamata et al 8 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations